2020
DOI: 10.1186/s12957-020-01843-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel ovarian cancer-specific fluorescent antibody probe for targeted near-infrared fluorescence imaging

Abstract: Background: To meet clinical needs, fluorescence-guided surgery has emerged as a new technique that guides surgeons in the resection of cancerous tissue by highlighting tumour lesions during surgery. We aimed to evaluate the novel ovarian cancer-specific antibody fluorescent probe COC183B2-800 (COC183B2 conjugated with IRDye800CW) in tumour-specific imaging to determine if it can help surgeons remove malignant lesions under fluorescence guidance. Methods: The expression of OC183B2 antigen in epithelial ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The COC183B2 monoclonal antibody was developed in our laboratory with independent intellectual property rights. Previously, we found that positive OC183B2 expression in 89.9% of EOC patients 13 . OC183B2 expression could be detected in the four main histologic types of EOC, serous, mucinous, clear cell, and endometrioid EOC, as well as in early‐stage and low‐grade EOC 13 .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The COC183B2 monoclonal antibody was developed in our laboratory with independent intellectual property rights. Previously, we found that positive OC183B2 expression in 89.9% of EOC patients 13 . OC183B2 expression could be detected in the four main histologic types of EOC, serous, mucinous, clear cell, and endometrioid EOC, as well as in early‐stage and low‐grade EOC 13 .…”
Section: Discussionmentioning
confidence: 88%
“…13 OC183B2 expression could be detected in the four main histologic types of EOC, serous, mucinous, clear cell, and endometrioid EOC, as well as in early-stage and low-grade EOC. 13 However, a previous report showed negative FR expression in mucinous EOC. 25 Clear cell and mucinous EOC tend to go undiagnosed, and they cannot be detected by PET/CT.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Chen et al demonstrated OC183B2 expression (61.2%-89.9%) in OC. 49,50 They subsequently developed COC183B2-Cy7 (Cy7-conjugated COC183B2) and COC183B2-800 (IRDye 800CW-conjugated COC183B2). 49,50 Interestingly, the two fluorescent probes showed relatively high fluorescence signals in the liver.…”
Section: Oc-associated Antigen (Oc183b2)mentioning
confidence: 99%
“…One approach to aiding surgical tumor removal focuses on targeting fluorescent probes specifically to ovarian cancer. The most clinically advanced strategy for fluorescent detection of ovarian tumors (but not yet approved) is conjugating a fluorescent dye to folate, which binds to folate receptors that are highly expressed in ovarian cancer cells. ,, However, over-expression of this receptor varies widely between different tumors, and it is present in lymph nodes and other normal tissue, leading to false-positive signals. Some efforts to lower false-positive signals involve using near-infrared (NIR) fluorophores. Although they produce better tumor-to-background ratios, they involve multicamera setups that must be processed in parallel in order to achieve real-time detection. …”
Section: Introductionmentioning
confidence: 99%